1999
DOI: 10.1046/j.1365-201x.1999.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased metabolism of infused 1‐methylxanthine by working muscle

Abstract: Exogenous substrates for capillary endothelial enzymes have potential as markers for changes in capillary recruitment (albeit nutritive flow). The metabolism of infused 1-methylxanthine (1-MX) to 1-methylurate (1-MU) by capillary endothelial xanthine oxidase of the constant-flow perfused rat hindlimb was shown previously to decrease with oxygen uptake (VO2) when nutritive flow was decreased. In the present study, the metabolism of 1-MX was investigated under conditions when VO2 and nutritive flow are known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…The metabolism of 1-MX, by the capillary endothelial enzyme xanthine oxidase, has been used previously by us as an indicator of nutritive flow (27,41). Figure 3 shows the effect of insulin, 5-HT, and the combination of insulin ϩ 5-HT on 1-MX metabolism, determined at the 80-min time point, when steady-state conditions have been attained (27).…”
Section: Resultsmentioning
confidence: 99%
“…The metabolism of 1-MX, by the capillary endothelial enzyme xanthine oxidase, has been used previously by us as an indicator of nutritive flow (27,41). Figure 3 shows the effect of insulin, 5-HT, and the combination of insulin ϩ 5-HT on 1-MX metabolism, determined at the 80-min time point, when steady-state conditions have been attained (27).…”
Section: Resultsmentioning
confidence: 99%
“…Others have shown that xanthine oxidase is predominantly located in capillary endothelial cells (29), and on this basis, we conducted experiments to see whether the metabolism of infused 1-MX, targeted for the capillary endothelial cells, changed in proportion to nutritive (capillary) flow. We found that when flow was predominantly non-nutritive, metabolism of 1-MX was markedly reduced (30), and when flow was predominantly nutritive, as with exercise, metabolism was increased (31). On this basis, 1-MX metabolism was used to assess changes in capillary recruitment due to insulin under normal conditions (21), when non-nutritive flow predominated (23), and in the presence of TNF-␣ (24).…”
Section: Discussionmentioning
confidence: 99%
“…Values are means±SE for n=8-10 in each group. *p<0.05 difference from Sal; # p<0.05 difference from Ins Xanthine oxidase activity Metabolism of 1-MX by xanthine oxidase of the hind limb muscle vasculature, which is measured under saturating conditions of 1-MX, has been shown to reflect changes in nutritive flow [25,28]. However, because conditions are saturating, a change in the level of xanthine oxidase activity could also influence the rate of metabolism of 1-MX.…”
Section: -Mx Metabolismmentioning
confidence: 99%